Tolerance for contradiction, gratitude and meaning-making towards frontline healthcare workers during COVID-19 - Yap, Maverick Shi Yee (Nanyang Technological University, 2021)
In this study, we examined the relationship between tolerance for contradiction and gratitude towards frontline healthcare workers and investigated the potential of meaning-making as the mediator. Tolerance for contradiction was not found to be related to gratitude in the main analysis. With the exception of a marginally significant relationship between the written expression of gratitude and tolerance for contradiction. However, exploratory analysis found that tolerance for contradiction was significantly related to one measure of gratitude, written expression of gratitude and marginally significantly related to another measure of gratitude, intent to pay back. There was no significant mediation effect for the variable of meaning-making. We discuss the implications for tolerance for contradiction and how it could help change the perception towards frontline healthcare workers, especially during the COVID-19 pandemic.